Addressing Challenges to Growth, Security and Stability Speech by World Bank Group President David Malpass at the Warsaw School of Economics - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by the World Bank Group President David Malpass, addressing Challenges to Growth, Security and Stability on April 12, 2022 at the Warsaw School of Economics. He spoke about again living through a dangerous period of overlapping crises and conflicts with Poland near the center. He has been deeply shocked and horrified at Russia’s invasion of Ukraine, the atrocities committed against the civilian population, and the loss of life and livelihoods for millions of Ukrainians. Since the invasion, the World Bank Group has provided fast-disbursing financial support to Ukraine to help the government provide critical services to people, including wages for hospital workers, pensions for the elderly, and social programs for the vulnerable. Through IFC, they have provided immediate working capital for companies providing supplies to Ukraine. He was pleased to announce that the World Bank is preparing a nearly 1.5 billion US dollars operation for Ukraine to support continuation of essential government services during the war. He also discussed about the following: (i) Overlapping global crises; (ii) Weakening economic outlook; (iii) Areas for action; and (iv) Lessons learned.